Photoviz : visualizing information through photography - Felton, Nicholas, ....- (Berlin : Gestalten, 2016)
The stories told with graphics and infographics are now being visualized through photography. Fotoviz shows how these powerful images are depicting correlations, making the invisible visible, and revealing more detail than classic photojournalism. Images are omnipresent in our digital age, but they're worth a closer look. Many of them can tell us stories in new and surprising ways. Fotoviz reveals how infographics and data visualization are currently impacting photography and points to innovative possibilities for the future. Today, data is being visualized through photographic techniques such as long and multiple exposures. Insightful information is being communicated by making a single image out of several different shots or using a 3D perspective. The work featured in Fotoviz, to cite only a few compelling examples, makes invisible Wi-Fi fields visible, allows airport flight activity from a full day to appear as if it were happening at once, and illustrates the average selfietaking behavior of an entire city.
Keywords: Fotografie ; foto's bewerken